Psychometric evaluation of the temporal experience of pleasure scale (TEPS) in a german sample - Simon, Joe J.; Zimmermann, Johannes; Cordeiro, Sheila; Marée, Ina; Gard, David E.; Friederich, Hans-Christoph; Weisbrod, Matthias; Kaiser, Stefan (Psychiatry research, 2018)
Anhedonia, or the inability to experience pleasure, is commonly observed in schizophrenia. It has been suggested that patients with schizophrenia are unable to predict future pleasurable events, but show intact experience of in-the-moment pleasure. Therefore, the Temporal Experience of Pleasure Scale (TEPS), a self-report measure allowing the assessment of anticipatory and consummatory pleasure, has been developed. To validate the German version of the TEPS, we recruited 59 healthy control participants and 51 patients with schizophrenia or schizoaffective disorder who completed the TEPS as well as a battery of psychometric tests to assess psychopathology, in particular self-rated anhedonia and clinician-rated apathy as well as overall measures of negative symptoms. We found acceptable to good internal consistency and a factor structure comparable to the original version. Scores of the TEPS were related to measures of anhedonia and apathy, but not with other measures of psychopathology. The present results suggest that the German version of the TEPS shows adequate reliability and validity to assess the construct of anhedonia. However, differential aspects of anticipatory and consummatory pleasure should be further investigated in clinical samples.